Modeling spatiotemporal dynamics of outbreaking species: influence of environment and migration in a locust. Issue 3 (1st March 2015) - Veran, Sophie; Simpson, Stephen J.; Sword, Gregory A.; Deveson, Edward; Piry, Sylvain; Hines, James E.; Berthier, Karine
Abstract : Many pest species exhibit huge fluctuations in population abundance. Understanding their large‐scale and long‐term dynamics is necessary to develop effective control and management strategies. Occupancy models represent a promising approach to unravel interactions between environmental factors and spatiotemporal dynamics of outbreaking populations. Here, we investigated population dynamics of the Australian plague locust, Chortoicetes terminifera, using density data collected between 1988 and 2010 by the Australian Plague Locust Commission over more than 3 million km 2 in eastern Australia. We applied multistate and autologistic multi‐season occupancy models to test competing hypotheses about environmental and demographic processes affecting the large‐scale dynamics of the Australian plague locust. We found that rainfall and land cover predictors best explained the spatial variability in outbreak probability across eastern Australia. Outbreaks are more likely to occur in temperate than tropical regions, with a faster and more continuous response to rainfall in desert than in agricultural areas. Our results also support the hypothesis that migration tends to propagate outbreaks only locally (over distances lower than 400 km) rather than across climatic regions. Our study suggests that locust outbreak forecasting and management systems could be improved by implementing key environmental factors and migration in hierarchical spatial models. Finally, our modeling framework can be seen as a step towards bridging the gap between mechanistic and more phenomenological models in the spatial analysis of fluctuating populations.